Bites of Burden: Snake Bite Envenoming in India, Regional Venom Differences, Treatment Efficacy and Health System Challenges: A Systematic Review Addressing Evidence Gaps - Avinash Z. Jaybhaye; Abhinov Thamminaina; Shikhar Verma; Hirani Yash Bharatbhai; Mario Antony; Rahul S.S.; Harikrishnan C. (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Snakebite envenomation is a neglected tropical disease causing substantial mortality in India, with an estimated 58,000 deaths annually, roughly half of global snakebite deaths. Important uncertainties remain regarding regional venom variation, species speci𿿿c antivenomrequirements, healthsystemperformance, economic burden, and effective community level interventions. Objectives: To systematically evaluate, the epidemiology and geographic distribution of snakebite envenomation in India and globally; clinical features, complications, and mortality associated with major venomous species; antivenom therapy practices, ef𿿿cacy, dosing, and adverse reactions; emerging innovations insnakebite management; and gaps in policy, public health response, and research priorities.Data sources: PubMed, Embase, Scopus, Web of Science, Google Scholar, and IndMed were searched from January 1990 to October 2025; reference lists of included articles and relevant reviews were also screened. Study eligibility criteria: Eligible studies were peer reviewed human research from India or neighbouring South Asian countries, including randomized and non randomized trials, cohort studies, crosssectional studies, and case series with at least 20 patients, reporting data on epidemiology, venom composition, clinical features, treatment, outcomes, costs, or community knowledge related to snakebite envenomation; single case reports, non peer reviewed opinions, and studies with unclear methods or incomplete outcome data were excluded. Study appraisal and synthesis methods: Two reviewers independently screened titles/abstracts and full texts and extracted data using a standardised form; disagreements were resolved by discussion or a third reviewer. Methodological quality was assessed using Joanna Briggs Institute critical appraisal tools appropriate to study design, with studies scoring at least 7/10 considered acceptable for quantitative synthesis. Random effects meta-analysis was used to pool treatment outcomes and mortality, heterogeneity was quanti𿿿ed withI², andsubgroup analyses explored the effects of snake species, geographic region, and time from bite to antivenom administration; funnel plots and Egger regression were used to assess publication bias. Results: Of 1,967 records identi𿿿ed, 100 studies met the inclusion criteria and85contributed data to metaanalysis. Cobra venom potency varied approximately 3.6 fold across India (lethal dose 0.35–1.25 mg/kg), paralleling regional differences in respiratory failure from 77% in northern India to 22% in southern India. Across 1,847 patients with species con𿿿rmed bites, mean antivenomuse was 8.9 ± 3.3 vials for cobras, 18.3 ± 6.8 for kraits, and 12.1 ± 4.5 for Russell’s viper, with krait bites showing markedly lower treatment success (41%) than cobras (94%). Each hour of delay from bite to antivenom administration reduced treatment success by about 3.2 percentage points, and national economic losses were estimated at `45–120 billion annually when direct and indirect costs were combined. Misidenti𿿿cationof snake species occurred in 20–30% of cases and was associated with about 2.5% absolute excess mortality due to inappropriate dosing, while emerging recombinant antivenoms and monoclonal antibodies remain at least 10–15 years away from widespread clinical use. Limitations: Most evidence came from retrospective hospital based studies in a limited number of high burden states, with sparse data from Northeast and Central India, limited longterm disability outcomes, and heterogeneity in outcome de𿿿nitions and economic methods. Conclusions: Snakebite mortality in India is driven less by venom potency than by modi𿿿able healthsystem and community factors, including delayedaccess toantivenom, non species speci𿿿c dosing, and frequent misidenti𿿿cation of bitingspecies. Immediate priorities are region and species speci𿿿c treatment protocols, reliable antivenom supply at 𿿿rst contact facilities, and scalable training or village health workers and clinicians, while future research should re𿿿ne regional venom characterization, update economic estimates, and evaluate digital and communitybased interventions. Registration: PROSPERO CRD420251168454